Réponses

2014-08-12T18:21:44+02:00
A) 2x(3-2x)+4(x+3)=6x-4x²+4x+12=-4x²+10x+12
b) -5(3-x)+8(4+x)=-15+5x+32+8x=13x+17
c) 7(2x+3)-4(3-x)=14x+21-12+4x=18x+9

32/40+45/36-3/2=4/5+5/4-3/2=16/20+25/20-30/20=11/20
Meilleure réponse !
  • Utilisateur Brainly
2014-08-12T18:28:29+02:00
Développer et réduire si possible : 

A=2x(3-2x)+4(x+3) \\ A=6x-4x^2+4x+12 \\ A=-4x^2+10x+12 \\  \\ B=-5(3-x)+8(4+x) \\ B=-15+5x+32+8x \\ B=13x+17 \\  \\ C=7(2x+3)-4(3-x) \\ C=14x+21-12+4x \\ C=18x+9

Calculer :

A= \frac{32}{40} + \frac{45}{36} - \frac{3}{2}   \\  \\ = \frac{4}{5} + \frac{5}{4} - \frac{3}{2}  \\  \\ = \frac{16}{20} + \frac{25}{20}- \frac{30}{20}   \\  \\ = \frac{41}{20} - \frac{30}{20}  \\  \\ \boxed{= \frac{11}{20}} (=0.55)